A question of time: the land snail Murella muralis (Gastropoda: Pulmonata) reveals constraints on past ecological speciation. Issue 1 (19th November 2012) - Fiorentino, V.; Manganelli, G.; Giusti, F.; Tiedemann, R.; Ketmaier, V.
Abstract The lively debate about speciation currently focuses on the relative importance of factors driving population differentiation. While many studies are increasingly producing results on the importance of selection, little is known about the interaction between drift and selection. Moreover, there is still little knowledge on the spatial‐temporal scales at which speciation occurs, that is, arrangement of habitat patches, abruptness of habitat transitions, climate and habitat changes interacting with selective forces. To investigate these questions, we quantified variation on a fine geographical scale analysing morphological (shell) and genetic data sets coupled with environmental data in the land snail Murella muralis, endemic to the Mediterranean island of Sicily. Analysis of a fragment of the mitochondrial DNA cytochrome oxidase I gene (COI) and eight nuclear microsatellite loci showed that genetic variation is highly structured at a very fine spatial scale by local palaeogeographical events and historical population dynamics. Molecular clock estimates, calibrated here specifically for Tyrrhenian land snails, provided a framework of palaeogeographical events responsible for the observed geographical variations and migration routes. Finally, we showed for the first time well‐documented lines of evidence of selection in the past, which explains divergence of land snail shell shapes. We suggest that time and palaeogeographical history acted as constraints in the progress along the ecological speciation continuum. Our study shows that testing for correlation among palaeogeography, morphology and genetic data on a fine geographical scale provides information fundamental for a detailed understanding of ecological speciation processes.